Meningitis/Meningoenzephalitis: ein Chamäleon in der Medizin - Meyding-Lamadé, Uta; Craemer, Eva Maria (Deutsche medizinische Wochenschrift, 2020)
A wide range of pathogens can cause meningitis or meningoencephalitis. Guiding symptoms of meningitis are headache, fever, nausea, vomiting and meningism. Guiding symptoms of meningoencephalitis are headache, fever, qualitative or quantitative disturbances of consciousness, signs of meningism are possible, optional focal neurological signs can occur. Crucial prognostic factor in treatment of acute meningitis and meningoencephalitis is rapid diagnosis and early initiation of therapy. An early start of therapy is crucial. In addition to rapid pathogen-specific treatment, specialized neurological intensive care medicine is life-saving